RELEVANSI MATA KULIAH ILMU BAHAN BANGUNAN TERHADAP BAHAN BANGUNAN DI DUNIA INDUSTRI - Anestasya Ayunda; Kusno Adi Sambowo (LPPM Universitas Negeri Jakarta, 2020)
Abstrak Penelitian ini bertujuan untuk meningkatkan nilai dan keterampilan siswa pada mata pelajaran Aplikasi Perangkat Lunak dan Desain Interior Gedung. Pelaksanaan penelitian tindakan kelas ini terdiri dari dua siklus (siklus I dan siklus II) dengan setiap siklus dilakukan dua kali pertemuan. Siswa melaksanakan pembelajaran berbasis proyek; Artinya, siswa langsung berlatih menggambar dengan lembar kerja yang disediakan. Peran tutor sebaya disini adalah membantu guru dalam membimbing siswa dalam menyelesaikan proyek, didampingi dan diarahkan oleh guru. Hasil yang diperoleh menunjukkan bahwa pada siklus I aspek keaktifan siswa mencapai rata-rata 76% (Cukup Aktif) dan ketercapaian nilai pengetahuan 17,1% siswa berkompeten. Sebagai perbandingan, pencapaian skor keterampilan adalah 25,7% siswa berkompeten dengan KKM (Kriteria Ketuntasan Maksimal) 76. Pada siklus II terjadi peningkatan yang signifikan dengan keaktifan siswa meningkat menjadi rata-rata 86% (Aktif), sedangkan pencapaian skor pengetahuan meningkat menjadi 91,43% siswa berkompeten dan pencapaian skor keterampilan juga meningkat dari segi ketuntasan belajar yaitu menjadi 94% siswa berkompeten. Kata kunci: Peningkatan Kompetensi, Tutor Sebaya, Project Based Learning Abstract In the current era of the development of the infrastructure industry, the building material industry in Indonesia has developed very rapidly along with the increasing national economic conditions and innovative technological advancements. In connection with this progress, resulting in increasing needed human resources, especially students who are able to have the knowledge, competencies, and expertise in accordance with the progress and development of the building materials industry. Given the demands and encouragement from the industrial world, the Building Material Science Course is expected to be a means to shape these competencies by looking at the relevance of the development of innovative building materials, so that graduates are expected to produce students who have up-to-date knowledge and competencies related to materials building in the industrial world. The purpose of this article is to increase knowledge and information related to the development of building materials, especially buildings in the industrial world, through the study of Building Materials Science. The method used is the literature review. Literature study results show that learning from lectures is able to contribute to the increase in knowledge and competencies related to the development of building materials that are relevant to the industrial world, one of which is the Building Materials Science Course. The more competence of students regarding building materials, the building in any form can be easily realized when working in the industrial world. Keywords: Relevance, Building Materials, Infrastructure, Industry